Escape from New York the official story of the film - Walsh, John 1971- (Titan Books, 2021)
"Over forty years after the release of the iconic hit, Escape from New York: The Official Story of the Film delves into the archives to showcase the creation of the movie. Directed by John Carpenter and released in 1981, Escape from New York thrilled audiences worldwide with its memorable characters, gritty premise and creative special effects. Escape from New York: The Official Story of the Film is the ultimate retrospective to the cult-classic movie. This must-have book intricately illustrated the production process of the science-fiction blockbuster, plus the impact and influence in popular culture, as well as the costuming, special effects, music, posters, and much more. Featuring brand new interviews with cast and crew, this extraordinary collection of never-before-seen art will give fans exclusive insight into every aspect of Escape from New York"--Dust jacket
Keywords: Escape from New York; Escape from New York (Motion picture); Bildband